Tanfīż Istirātījiyyah Muṭābiqah Biṭāqah Fihris (Index Card Match) liṭullāb al-Ma’had: The Implementation of Index Card Match Strategies for Students at Islamic Boarding Schools - Rahmawati, Fitra Awalia; Winata, M. Sidik Niki; Mulyanto, Dedi (Study Program of Arabic Language Teaching, 2023)
This study aims to explain increased student learning outcomes and activeness by applying the Index Card Match strategy to the Nahwu lessons. This research is called Classroom Action Research. This research was carried out twice with four steps: planning, preparation for teaching in class, implementation of the teaching process in class, observation of students' conditions, and reflection by researchers to analyze the results of observations. The research location is the Al-Khair Ponorogo Modern Islamic Boarding School in class 2, with 20 students. In collecting data, researchers interviewed school principals and teachers to obtain information regarding student and school conditions. In the observation, the researcher recorded the conditions before and after implementation. In tests prepared by teachers related to nahwu. The data analysis used is quantitative and qualitative. The results of this study show that student learning outcomes increased by 20%. And increase student activity with a ratio of 12.5% ​​increase in student activity.